(untitled) (Canadian Oncology Today, 2024)
For decades, the cornerstone for treatment of advanced urothelial carcinoma (aUC) has consisted of platinum-based chemotherapy regimens, such as GC (gemcitabine plus cisplatin/carboplatin) or MVAC (methotrexate, vinblastine, doxorubicin, and cisplatin). Thereafter, immune checkpoint inhibitors (ICI) were incorporated into the standard of care, initially as monotherapy in subsequent-line settings and more recently as maintenance treatment with chemotherapy in the first-line setting. Recently, the development of antibody-drug conjugates (ADCs) has dramatically shifted the treatment landscape for aUC. ADCs are engineered to function as a biologic “honing missile”, with the aim of delivering its cytotoxic payload to the target cancer cell while remaining stable in circulation and minimizing off-target toxicity. Enfortumab vedotin was the first to demonstrate efficacy in urothelial carcinoma (UC), initially as monotherapy and later in combination with ICI, surpassing the decades-old standard of first-line chemotherapy. The aim of this review is to discuss the evolving field of ADCs in aUC, highlighting the main targets, clinical data, toxicities, and future opportunities. ADCs are engineered to function as a biologic “honing missile”, with the aim of delivering its cytotoxic payload to the target cancer cell while remaining stable in circulation and minimizing off-target toxicity. Enfortumab vedotin was the first to demonstrate efficacy in urothelial carcinoma (UC), initially as monotherapy and later in combination with ICI, surpassing the decades-old standard of first-line chemotherapy. The aim of this review is to discuss the evolving field of ADCs in aUC, highlighting the main targets, clinical data, toxicities, and future opportunities.